Tratak – A Yoga Kriya For Eye Sight And Stress In Modern Era - Shrivatava, Manindra Mohan; Sharma, Anita; Tripathi, Sasmita; Pali , Vibha (International Research Journal of Ayurveda & Yoga, 2021)
The way to solid life is having a sound brain. We are living in a quick moving age. Contamination, stress and undesirable way of life are basic issues of the present period. Refractive Error occurs when the eyes are unable to focus images clearly on the retina. These eye disorders are most common in children, but they can affect people of any age. Because of today’s lifestyle, which includes increased use of computers, television, and cell phones, the eyes are subjected to a great deal of strain. As a result, now is the time to shield and save your eyes from refractive errors (such as myopia, hypermetropia, presbyopia, astigmatism). Stress can be felt anyplace we go and whatever we do. What’s more, since wellbeing and stress are connected, we may feel certain repercussion on body i.e.- gloom, headache, hypertension, heart issues and so on Reflection is end up being an incredible method to accomplish pressure the board, which manages psychological well-being than physical. They have numerous physical and mental complexities, which can be manage refinement strategies of yoga. The Shatkarmas of Yoga are vital to clean body and brain Trataka (to gaze steadily at a fixed point) is one of the six karmas of yoga (The Shatkarma) for filtration of body and brain. Trataka (to gaze steadily at a fixed point) is additionally a kind of contemplation which includes ceaseless looking at any article or point. It can help us see better by encouraging mental concentration and strengthening and calming our eye muscles, which are in charge of regulating our eyeball movements.